Evaluating undergraduate understanding of dental anatomy, histology and oral pathology: a survey-based study - Khanam, Wajiha; Anjum, Rubeena; Vijay, Pradakhshana; Singh, Priyanka; Pardhe, Nilesh D.; Jehan, Ayeda (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Dentistry is a progressive field of medicine focused on studying, diagnosing, preventing, and treating diseases and disorders of the oral cavity and maxillofacial region. While an understanding of anatomy and histology is crucial for dental practice, dental students often view oral histology, oral anatomy, and oral pathology as less important for their careers and more difficult to grasp. However, a deeper knowledge of this subject enhances comprehension and aids in the diagnosis and treatment of cases. Still, there remains a gap in understanding and interest among students. This may be partly attributed to the perception that these subjects are non-clinical and offer limited opportunities for practical application. The study aims to assess undergraduate students’ comprehension of dental anatomy/histology and oral pathology and identify specific areas where they encounter difficulties connecting with the subject matter. Methods: This question-based cross-sectional study was conducted in the institute, and it included 116 undergraduate students. Results: The Chi-square analysis revealed several significant associations between the academic year of students and their responses to questions related to oral pathology, dental anatomy, and forensic odontology. Conclusions: The quality of education must be upheld, with a focus on creating a nurturing and supportive learning environment. This can be achieved through gathering student feedback and continuously refining the curriculum.